DETERMINAN NILAI PERUSAHAAN PADA PT ANTAM, TBK - Irwandi, Miladatul Husni; Nasrul Kahfi Lubis; Mayang Murni (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study aims to determine the influence of Corporate Social Responsibility (CSR) Disclosure, Company Size, and Profitability on Company Value at PT. Antam Tbk. The object of this research is PT Antam Tbk. The sampling technique used is saturated sampling. The data collection method is based on the company's historical data, namely the financial data audited by PT. Antam Tbk, which is listed on the Indonesia Stock Exchange (IDX) for the period 2009-2023. The data analysis method used in this research is multiple linear regression analysis using SPSS software. The results of this study show that the variable of Corporate Social Responsibility (CSR), company size and profitability disclosure has a positive and significant effect on the company value at PT. Antam Tbk. Simultaneously, the disclosure of corporate social responsibility (CSR), company size, and profitability have a significant effect on the company value at PT. Antam Tbk. Limitations in this study include a research period that is too long so that there is missing and incomplete data which ultimately affects the analysis and generalization of findings. based on these limitations, it can be suggested to conduct a comparative study or shorten the research period.